Los costos de producción de banano y su repercusión en la rentabilidad de la hacienda san honorato de la compañía honorasa S.A. del Cantón El Empalme en el periodo 2010 - Holguín Aguas, Jesica Amira (2012)
The Company Honorasa S. A., domiciled in the city of Guayaquil in the streets and the River Gold, which is part of the Hacienda San Honorato, it is located at km 10 via the canton The Junction - Guayaquil, with 193 ha-1 whose economic activity is to engage in planting, harvesting and packing of bananas. This project aims to analyze the costs of banana production and determine the range of impact on the profitability of the business cycle of the hacienda San Honorato during 2010, because currently takes no efficient control in the management of materials and inputs used in the production process. During the analysis of production costs could be determined that there 129.200.45 profitability dollars in the year 2010, it should be noted that we must make the necessary deductions such as income tax, profit sharing and the proportion of reserves legal and statutory, there is a cumulative loss of - $ 8,593.50 from previous years, which appears on the balance of the period, as a result of falling profits after taxes worth $ 70.422.32. In order to generate strategies to optimize costs, which collect information relevant to the balance sheets and profit and loss statement of the hacienda San Honorato of 2010, the same ones that were carefully analyzed each item and demonstrating their respective graphs, noting incidents margins relevant costs. Besides financial ratios were applied, showing that the same company is able to solvency year terms, as shown in its financial statements, although the income statement indicates a favorable economic position. To sustain the problem and hypotheses of the research was necessary to use primary and secondary sources and tools and techniques such as direct observation, interviews used a pre-structured interview guide with closed questions that supports the development of target variables study, for which established a form of interview, according to the research objectives. The target population of the research was three people; manager, accountant and assistant accountant, the analysis concludes that spring in our country is characterized by falling many rains and high humidity, while in the summer, high temperatures , more light and strong winds, causing water shortages and pollution, these issues directly affecting our banana plantations. The cost of fertilization of a hectare of bananas annually costs $ 879.60 each has and depends on weather conditions and the population factor. It has areas suitable for the treatment of waste generated in the production of bananas, the control system of current information on the farms is poor, work systems are inadequate, ie traditionally performed manually or in estates, for it was necessary that the estates analyze profitability in order to strengthen and unify the accounting, statistical controls policies and procedures.